Professionnalisme et rugby de haut niveau : approche anthropobiologique - Frédéric Bauduer; Caroline Monchaux; Jean-Pierre Mathieu (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Until recently rugby has traditionally represented the regions and has been an outstanding example of amateur sport. Its recent change to professionalism, mainly imposed by the media and business lobbies, has resulted in profound changes in the anthropometric and psychological characteristics of the players and the place of this sport in society. These recent changes in the high-level rugby player and his sport are discussed, based on a study carried out on two elite French teams and a comparative retrospective analysis.